1992
DOI: 10.1002/gps.930070105
|View full text |Cite
|
Sign up to set email alerts
|

Major depression in hospitalized medically ill older men: Documentation, management, and outcome

Abstract: SUMMARYFifty-three hospitalized elderly men with medical illness were diagnosed with major depressive disorder and followed up for a mean of 2.3 months. Documentation and management of the depression by medical housestaff during the followup period were examined. There was no note of depression in the medical records of 44% of depressed patients, and depression was on the active problem list of only 32%. Followup and management plans for the depression after discharge were documented in 29%. No form of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
47
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
12
47
1
Order By: Relevance
“…The data agree with the results of previous studies conducted in this field [23][24][25][26]. The difference in survival between the 'independent' group (median = 35 months) and the community-dwelling reference group (median = 95 months) highlights the frailty of psychogeriatric patients suffering from cognitive function disorders in conjunction with psychiatric function disorders.…”
Section: Discussionsupporting
confidence: 82%
“…The data agree with the results of previous studies conducted in this field [23][24][25][26]. The difference in survival between the 'independent' group (median = 35 months) and the community-dwelling reference group (median = 95 months) highlights the frailty of psychogeriatric patients suffering from cognitive function disorders in conjunction with psychiatric function disorders.…”
Section: Discussionsupporting
confidence: 82%
“…In the usual-care group, the rates of request for psychiatric consultation and antidepressant therapy prescribed at discharge were 26.6% and 35.5%-45.2%, respectively, much higher than reported in descriptive studies. 3,12,13 Controvertibly, the rate of antidepressant use in the usual-care group was high (29%-35.5%) on admission.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent benefits of treatment, 11 up to 90% of cases of depression are not detected by attending physicians during the course of usual hospital care, 3,12 and few patients receive optimal treatment in hospital or after discharge. 12,13 Because a strategy of systematic detection and treatment has been shown to benefit elderly people with depression living in the community, [14][15][16][17][18] we conducted a randomized clinical trial to evaluate whether systematic detection and multidisciplinary treatment of depression could be effective in reducing symptoms of depression and improving mental and physical health status in elderly medical inpatients. Our secondary objective was to determine the effect of the intervention on basic and instrumental activities of daily living, cognitive status, side-effects profile, mortality and health services utilization (length of hospital stay, and number of readmissions and emergency department visits).…”
mentioning
confidence: 99%
“…Rates of improvement of depression in three surveys composed exclusively of male American veterans (Schuckit et al, 1980;Rapp et al, 1991;Koenig et al, 1992) were 33%, 35% and 36% respectively. Although depression improved in 55% of the 11 men in our sample, the dierences are probably not signi®cant given that the numbers involved were small, ranging between six (Schuckit et al, 1980) and 33 (Koenig et al, 1992).…”
Section: Outcome Of Depressionmentioning
confidence: 97%
“…Although nine surveys of depressive disorder among acutely ill medical/surgical inpatients aged 65 and older have included a longitudinal component (Bergmann and Eastham, 1974;Schuckit et al, 1980;Cooper, 1987;Koenig et al, 1989;Rapp et al, 1991;Antonelli et al, 1991Antonelli et al, , 1992Koenig et al, 1992;Evans, 1993), only four reported aective state as an outcome (Schuckit et al, 1980;Rapp et al, 1991, Koenig et al, 1992Evans, 1993) and three of these four enrolled men only. Thus, the purpose of this 1-year follow-up survey of depressed patients identi®ed in a crosssectional study (Fenton et al, 1994) was to determine the outcome of major depressive episode (MDE) among male and female inpatients separately and de®ne characteristics that distinguished between patients whose depression did and did not improve (prognostic factors).…”
mentioning
confidence: 96%